A Phellinus baumii–based supplement containing Salvia miltiorrhiza Bunge improves atherothrombotic profiles through endothelial nitric oxide synthase and cyclooxygenase pathways in vitro and in vivo. (June 2016) - Lim, Yeni; Lee, Sena; Kim, Ji Yeon; Shin, Jae-Ho; Kwon, Oran
Highlights: The PS is a combination supplement [ P. baumi (PB) plus S. miltiorrhiza Bunge (SM)]. A rat platelet activation model and cells were employed to test the hypothesis. The PS showed an additive and positive effect on eNOS and COX pathway. The effect was attributed to the differential mode of action between PB and SM. The data suggest potential use of PS to maintain endothelial and vascular health. Abstract: Given the high prevalence of atherothrombotic disease and increasing attention to functional foods, we tested the hypothesis that a combination supplement (PS) containing Phellinus baumii (PB) and Salvia miltiorrhiza Bunge (SM) may improve the atherothrombotic profile in rats. The PS (Experiment 1) or PB/SM (Experiment 2) supplement was administered orally once daily for 7 days prior to inducing platelet activation at the last day. Orally administered PS showed an additive and positive effect on nitric oxide (NO) availability, adhesion molecule/pro-inflammatory cytokine release, and thrombosis compared to controls. This effect was attributed more to PB than to SM for cyclooxygenase (COX)-1 and to SM for COX-2. In vitro data revealed that tanshinone IIA derived from SM remarkably suppressed COX-2, and protocatechuic acid derived from PB caused a small increase in NO production. The data suggest the potential use of PS to ameliorate endothelial and vascular dysfunction induced by unintended platelet activation.